Implementation and Coordination Strategy of Overcurrent Protection - Sanusi @ Ikhsan, Mohd Hamim; Sidek, Azmi (Multidisciplinary Applied Research and Innovation, 2020)
This work reports an adaptive overcurrent relay with new adaptive function. The target of the adaptation procedure is to enhance the sensitivity of time overcurrent relays. The adaptive relay has an enhanced sensitivity and decreased processing time. Various AN based algorithm for control strategy are discussed. The main objective of developing AN based algorithm is to eliminate miscoordination and improve sensitivity of OC protection.  The control strategy varied according to the system topology and protection area covered. Adaptive function of the control strategy is available for connected or isolated system, thus providing more flexible system. The modification required for the proposed algorithm is minimal thus minor change in the relay’s firmware and without an increase in cost.